Theorem of Joint Variation


Here we will discuss about the Theorem of Joint Variation with the detailed explanation.

Theorem of Joint Variation: If x ∝ y when z is constant and x ∝ z when y is constant, then x ∝ yz when both y and z vary.

Proof: Since x ∝ y when z is constant Therefore x = ky where k = constant of variation and is independent to the changes of x and y.

Again, x ∝ z when y is constant.

or, ky ∝ z when y is constant (since, x = ky).

or, k ∝ z (y is constant).

or, k = mz where m is a constant which is independent to the changes of k and z.

Now, the value of k is independent to the changes of x and y. Hence, the value of m is independent to the changes of x, y and z.

Therefore x = ky = myz (since, k = mz)

where m is a constant whose value does not depend on x, y and z.

Therefore x ∝ yz when both y and z vary.


Note: (i) The above theorem can be extended for a longer number of variables. For example, if A ∝ B when C and D are constants, A ∝ C when B and D are constants and A ∝ D when B and C are constants, thee A ∝ BCD when B, C and D all vary. 


(ii) If x ∝ y when z is constant and x ∝ 1/Z when y is constant, then x ∝ y when both y and z vary.


Some Useful Results:

Theorem of Joint Variation

(i) If A ∝ B, then B ∝ A.

(ii) If A ∝ B and B∝ C, then A ∝ C.

(iii) If A ∝ B, then Aᵇ ∝ Bᵐ where m is a constant.

(iv) If A ∝ BC, then B ∝ A/C and C ∝ A/B.

(v) If A ∝ C and B ∝ C, then A + B ∝ C and AB ∝ C²

(vi) If A ∝ B and C ∝ D, then AC ∝ BD and A/C ∝ B/D



Now we are going to proof the useful results with step-by-step detailed explanation

Proof: (i) If A ∝ B, then B ∝ A.

Since, A ∝ B Therefore A = kB, where k = constant.

or, B = 1/K ∙ A Therefore B ∝ A. (since,1/K = constant)


Proof: (ii) If A ∝ B and B ∝ C, then A ∝ C.

Since, A ∝ B Therefore A = mB where, m = constant

Again, B ∝ C Therefore B = nC where n= constant.

Therefore A= mB = mnC = kC where k = mn = constant, as m and n are both Constants.

Therefore A ∝ C.

Proof: (iii) If A ∝ B, then Aᵇ ∝ Bᵐ where m is a constant.

Since A ∝ B Therefore A = kB where k= constant.

Aᵐ = KᵐBᵐ = n ∙ Bᵐ where n = kᵐ = constant, as k and m are both constants.

Therefore Aᵐ ∝ Bᵐ.

Results (iv), (v) and (vi) can be deduced by similar procedure.

Summarisation:

(i) If A varies directly as B, then A ∝ B or, A = kB where k is the constant of variation. Conversely, if A = kB i.e., A/B = k where k is a constant, then A varies directly as B.

(ii) If A varies inversely as B, then A ∝ 1/B or, A= m ∙ 1/B or, AB= m where m = constant of variation. Conversely, if AB = k (a constant), then A varies inversely as B.

(iii) If A varies jointly as B and C, then A ∝ BC or A = kBC where k = constant of variation.

Theorem of Joint Variation

 Variation




11 and 12 Grade Math 

From Theorem of Joint Variation to HOME PAGE


New! Comments

Have your say about what you just read! Leave me a comment in the box below. Ask a Question or Answer a Question.